Pembentukan Kebiasaan Positif dengan Nilai-Nilai Pancasila dalam Kehidupan Sehari-hari - Alya Putri Ardani; Duha Naufal Zacky; Muhammad Azzura Al Karazi; Safrilia Alvi Kartika; Vania Afiya Riannisa; Yayang Furi Furnamasari (Pusat Riset dan Inovasi Nasional, 2024)
This article was created with the aim of analyzing the importance of Pancasila values ​​in shaping the character and behavior of Indonesia's young generation. The main aim is to show how Pancasila can be used as a moral and ethical basis for everyday life, as well as a solution to various social problems faced by today's young generation, such as drugs, crime and promiscuity. This research uses qualitative methods, examining various related matters. The results of the research show that in everyday life, Pancasila does not play a role in law, but Pancasila is binding, this means that Indonesian citizens are bound to the ideals of realizing the vision of Pancasila, which is based on Belief in One Almighty God, Humanity, Unity, Interest and Justice. To achieve this, one solution is to create positive things based on Pancasila values.